Sceptical Notes on Uzawa's "Optimal Growth in a Two-Sector Model of Capital Accumulation", and a Precise Characterization of the Optimal Path - Haque, W. (Review of Economic Studies, 1970)
Journal Article Sceptical Notes on Uzawa's “Optimal Growth in a Two-Sector Model of Capital Accumulation”, and a Precise Characterization of the Optimal Path Get access W. Haque W. Haque University of Toronto Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 3, July 1970, Pages 377–394, https://doi.org/10.2307/2296727 Published: 01 July 1970 Article history Received: 01 May 1967 Revision received: 01 November 1969 Published: 01 July 1970